Postdoctoral researchers' perspectives on working conditions and equal opportunities in German academia - Davidson, Jacob D.; de Oliveira Lopes, Felipe Nathan; Safaei, Sajjad; Hillemann, Friederike; Russell, Nicholas J.; Schaare, H. Lina (Frontiers in Psychology, 2023)
Germany is a global research leader, with a per-country research output that ranks 3 rd worldwide, just behind China and the United States [1]. Postdoctoral researchers (postdocs) are an essential component of the scientific workforce in German universities and research institutions and play a vital role in advancing knowledge and innovation. However, the experiences of postdocs and other early career researchers (ECRs) indicate that working conditions pose a significant challenge to the pursuit of a long-term research career in Germany -particularly for international scientists and those from marginalized groups. We examine how unstable working conditions as well as insufficient structural support for equal opportunities and diversity are significant obstacles for the career development of ECRs in German academia. We discuss these issues with the aid of an extensive survey recently conducted and published by PostdocNet, a target-group network representing the interests of postdocs across Germany's Max Planck Society. The survey drew responses from 659 postdoctoral researchers working at the Max Planck Society and represents one of the few datasets of postdoctoral researchers' perspectives in Germany. Building on these findings, we suggest actions at governmental, institutional, and individual levels to improve the working conditions of postdoctoral researchers in Germany.